Simplify <span>22\times 2<span>22×2</span></span> to <span>44<span>44</span></span>
<span><span>{x}^{4}+44-16x-12<span><span>x<span><span>4</span><span></span></span></span>+44−16x−12</span></span>Collect like terms
<span><span>{x}^{4}+(44-12)-16x<span><span>x<span><span>4</span><span></span></span></span>+(44−12)−16x</span></span> Simplify</span><span><span>{x}^{4}+32-16x<span><span>x<span><span>4</span><span></span></span></span>+32−16x</span></span><span>
</span></span></span>
Answer:
2/5
Step-by-step explanation:
Answer:
x = 10
y = 70
Step-by-step explanation:
By using the vertical angles theorem we know that x+ y +10 = 90, also simplified to x + y = 80
and 2x + y = 90
By using the substitution method on x + y = 80, it will be y = -x + 80
When you put into the equation 2x + y = 90 you will get 2x -x +80 = 90
Then it will simplify to x = 10
After that plug 10 into x + y = 80 to 10 + y = 80 and get y = 70
Yes they do. In order to do this you must make the fraction 70/2 and 105/3. If you divided each one of those you get 35 for both which means it's a proportion.
The answer is 6.
To do this, remember PEMDAS?
You would first have to add what is in the parenthesis THEN do -3 + 9 to get 6.